Molecular Characterization of Pasteurella multocida Isolates from Ducks in Kerala - Antony P X (Department of Microbiology, College of Veterinary and Animal Sciences, 2004)
Twenty-five isolates from ducks and one from fowl were characterized as P. multocida using standard bacteriological procedures. A reference chicken strain (LKO) obtained from IVRI was used for comparison. All the avian isolates were found to be pathogenic for mice. Variation in fermentation patterns of dulcitol, mannitol, sorbitol and trehalose allowed the 27 isolates to be grouped into ten biovars. Two biotypes P. multocida subsp. septica, and P. multocida subsp. multocida were observed among the avian examined. All the isolates were uniformly sensitive to enrofloxacin, chloramphenicol and pefloxacin. Eight isolates from ducks and one from fowl have been serotyped as A:1. A species-specific PCR assay was used to confirm the identity of the isolates. Performing PCR on template DNA prepared from blood smears was found to be an extremely rapid method of diagnosis for pasteurella. No polymorphism within the KMT1 gene could be demonstrated by restriction analysis of PM-PCR product with Hae III. Restriction endonucleases analysis of genomic DNA of all the avian isolates with Hpa II and Hha I revealed three profiles each. The fowl isolates had a profile that was common to majority of the duck isolates. Eighty-eight per cent of the isolates carried plasmids. Two plasmid profiles were observed among the isolates examined. All the avian isolates showed a single REP-PCR profile indicating a high level of homogeneity among them. The outer membrane protein profiles of all the avian isolates were similar. Two protein fractions with molecular weights of 37.15 and 26.36 kDa were identified as the major OMPs by SDS-PAGE.